Crystallization of organic compounds : an industrial perspective - Tung, Hsien-Hsin; Paul, Edward L.; Midler, Michael; McCauley, James A.; John Wiley & Sons (Hoboken, New Jersey : Wiley, 2023)
'Organic compounds are defined for the purpose of this book as specialty chemicals that include pharmaceuticals and other fine chemicals. Purification and isolation via Crystallization of these materials is often challenging because of diversity of molecules and tight quality requirement of these materials. Specific examples of techniques developed for dealing with difficult situations and on an industrial perspective are presented'--
Includes index.
Keywords: Crystallization -- Industrial applications; Pharmaceutical chemistry; Pharmaceutical industry